A new species of the genus Aegyptobia (Acari: Tenuipalpidae) from Lorestan province, Iran - Iman Hassanvand; Shahriar Jafari; Masoumeh Khanjani; Mohammad Khanjani (Persian Journal of Acarology)
Aegyptobia gotohi sp. nov. is described and illustrated based on female specimens collected from barberry bushes, Berberis sp. (Berberidaceae) in Nurabad, Lorestan province, Iran.